(untitled) (Iraqi Journal of Medical Sciences, 2024)
Background: Diabetic nephropathy (DN) is a serious consequence of diabetes that can result in end-stage renal failure. The development of this condition is characterized by the activation of inflammatory pathways, in which pyroptosis, a specific type of programmed cell death, plays a vital role. Gasdermin D plays a crucial role in the process of pyroptosis, which is becoming more and more associated with DN. Elevated glucose levels and advanced glycation end-products stimulate the nucleotide-binding oligomerization domain - like receptor protein 3 inflammasome, resulting in the activation of caspase-1 and pyroptosis in different types of kidney cells. Objective: To investigate the role of pyroptosis in DN by evaluation of serum Gasdermin D level and biochemical parameters. Methods: This study was case-control study that had 160 individuals divided into three groups including 40 individuals with DN, 40 individuals with type 2 diabetes mellitus (T2DM), and 80 individuals as control group. The parameters total cholesterol (TC), triglyceride (TG), high-density lipoprotein-cholesterol (HDL-C), very low-density lipoprotein-cholesterol (VLDL-C), low-density lipoprotein-cholesterol (LDL-C), random blood sugar (RBS), glycated hemoglobin (HbA1c%), urea, and creatinine, GSDMD and IL-18) were examined in this study. Results: The study revealed a strong association between DN and the control group in all investigated parameters. The comparison between DM and the control group did not yield a statistically significant result for GFR, whereas other parameters did reveal significant results. The link between DN and DM is found to be substantial in terms of urea, creatinine, GFR, GSDMD, and IL-18. However, the remaining parameters also exhibit significant results. Conclusion: The significant result in all parameters shown in comparison between DN and control group due to elevated levels of parameters in DN patients. The non-significant result in (GFR) in comparison between DM and control group while other parameter shown significant result due to elevated levels of parameters in DM patients. Keywords: GSDMD, IL-18, DN, T2DM, pyroptosis Citation: Al-Tu’ma AF, Al-Wasiti EAR, Al-Saegh RM. Evaluation The serum level of Gasdermin D in relation to pyroptosis in diabetic nephropathy. Iraqi JMS. 2024; 22(2): 395-406. doi: 10.22578/IJMS.22.2.24